2022
DOI: 10.48550/arxiv.2206.02739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting and Understanding Human Action Decisions during Skillful Joint-Action via Machine Learning and Explainable-AI

Abstract: This study uses supervised machine learning (SML) and explainable artificial intelligence (AI) to model, predict and understand human decision-making during skillful joint-action. Long short-term memory networks were trained to predict the target selection decisions of expert and novice actors completing a dyadic herding task. Results revealed that the trained models were expertise specific and could not only accurately predict the target selection decisions of expert and novice herders but could do so at time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…35 This includes identifying what task information supports effective action decisions. [36][37][38] Recently, Auletta et al 39 have provided evidence suggesting that these challenges can be addressed using cutting-edge Supervised Machine Learning (SML), Long-Short Term Memory (LSTM) artificial neural networks, and explainable-AI (Artificial Intelligence) techniques. Specifically, the authors demonstrated how SML trained LSTM networks can not only be trained to predict the action decisions of individuals during team activity, but that an analysis of the resultant models using the explainable-AI technique, SHapley Additive exPlanation (SHAP), 40 can also identify and differentiate the sources of information that underlie the action decisions of expert and non-expert actors.…”
Section: Discerning Perceptual Features For Decision-making Using Exp...mentioning
confidence: 99%
“…35 This includes identifying what task information supports effective action decisions. [36][37][38] Recently, Auletta et al 39 have provided evidence suggesting that these challenges can be addressed using cutting-edge Supervised Machine Learning (SML), Long-Short Term Memory (LSTM) artificial neural networks, and explainable-AI (Artificial Intelligence) techniques. Specifically, the authors demonstrated how SML trained LSTM networks can not only be trained to predict the action decisions of individuals during team activity, but that an analysis of the resultant models using the explainable-AI technique, SHapley Additive exPlanation (SHAP), 40 can also identify and differentiate the sources of information that underlie the action decisions of expert and non-expert actors.…”
Section: Discerning Perceptual Features For Decision-making Using Exp...mentioning
confidence: 99%